A new method for reducing 5G overlapping coverage of urban grid roads - Yejiang ZHANG; Jie CHEN; Yi LIU; Xingzheng LI; Fuyang LI; Jian HU (Dianxin kexue)
The 5G network for urban grid road scenes has entered a new stage of refined operation and maintenance.The main contradiction has also shifted from insufficient coverage to severe overlapping coverage of some road sections.5G overlapping coverage will have a significant impact on users’ basic services such as internet access and voice.The optimization of traditional road overlapping coverage has many problems, such as inconsistent standards, recurring problems, and low work efficiency.The concept of overlapping coverage contribution was proposed, and an algorithm for root cause analysis of overlapping coverage was designed based on expert experience.An IT platform for optimizing overlapping coverage problems was also developed.The practice has proven that this method can effectively reduce the 5G overlapping coverage rate of urban grid roads, help enterprises save network optimization costs, and truly achieve the goal of cost reduction and efficiency increase.